Synovial chondromatosis of the temporomandibular joint - Bukhsh, Ayman Thafar; Alzaid, Sarah Abdullah; Alshawaf, Hussain Tawfiq; Asiri, Mohammed Abdullah; Nayyaz, Ammar Abdulaziz; Alfaifi, Asma Ali; Aldail, Saad Awdah; Almotairi, Tail Alhumaidi; Al Bu kafitah, Ali Ahmed; Alqahtani, Saud Ali; Almoslamany, Abdulaziz Mohammed (International Journal Of Community Medicine And Public Health, 2023)
When cartilage-like tissue is present in the synovial membrane of joints, it is known as synovial chondromatosis (SC). The main cause is believed to be the metaplasia of embryonal mesenchymal tissue in the synovial membrane. The metaplastic foci grow within the joint space and can detach from the synovial wall, forming free-floating bodies. While SC is more commonly associated with trauma in the temporomandibular joint (TMJ), the exact relationship between trauma and SC remains unclear. Improved diagnostic techniques, such as CT and MRI, have led to increased recognition of SC in the TMJ. Gender differences in the prevalence of TMJ SC have been observed, with women being more affected. Diagnosis involves imaging techniques like X-rays, CT scans, MRIs, and surgical removal of loose bodies is the preferred treatment. Arthroscopy is recommended for small, isolated loose bodies, while open surgery may be necessary for complete removal. Long-term follow-up is essential to monitor for recurrence. Histopathological findings reveal a mixture of cartilage and bone, with ossification and calcification present.